2019
DOI: 10.1103/physrevlett.122.248101
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in a Single Supported Phospholipid Bilayer: Real-Time Determination by Neutron Reflectometry

Abstract: Time-and temperature-resolved neutron reflectometry allowed us to perform the real-time characterization of the structural changes taking place across phase transitions in solid supported-lipid bilayers (SLBs). We identified the presence of an isothermal phase transition, characterized by a symmetrical rearrangement of lipid molecules in both bilayer leaflets, followed by the main thermotropic phase transition, and characterized by an independent melting of the two leaflets. We demonstrated that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…During the incubation, time-resolved measurements were performed acquiring the NR data every 5 min for a total duration of 1 h. These measurements were performed on a restricted Q-range ( Figure S2 ) and using an instrumental configuration that is described elsewhere. 46 At the end of the incubation period, the system was characterized, on the full Q-range, in D 2 O before rinsing, and then in D 2 O and SiMW after rinsing. In all of the steps (see Figure S2 ), no changes were observed, supporting the conclusion that frequency variations in QCM-D data were induced by a viscosity change and not by caffeine adsorption/adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…During the incubation, time-resolved measurements were performed acquiring the NR data every 5 min for a total duration of 1 h. These measurements were performed on a restricted Q-range ( Figure S2 ) and using an instrumental configuration that is described elsewhere. 46 At the end of the incubation period, the system was characterized, on the full Q-range, in D 2 O before rinsing, and then in D 2 O and SiMW after rinsing. In all of the steps (see Figure S2 ), no changes were observed, supporting the conclusion that frequency variations in QCM-D data were induced by a viscosity change and not by caffeine adsorption/adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…It was correspondingly proposed that the interaction with the support modifies lipid order in the proximal leaflet. A recent neutron reflectometry study, however, revealed only minor leaflet asymmetry in the main melting transition due to the presence of the substrate (69). It is thus unclear whether the viscosities of the two leaflets should differ substantially in SLBs, and the answer may be very system dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Eq. (1), to cover a q z -range from 0.085 to 3.5 nm À1 , two angular configurations were used (h ¼ 0:8 and h ¼ 3:2 ) with sample environment conditions following those presented in the literature [52]. MARIA, a monochromatic reflectometer, was utilized with two wavelengths, namely 0.5 nm and 1 nm, selected by a rotating velocity selector, defining a Dq z / q z = 10% resolution.…”
Section: Neutron Reflectometrymentioning
confidence: 99%